2008
DOI: 10.1182/blood-2007-08-107300
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 is up-regulated by CCL21/CCR7 interaction via extracellular signal-regulated kinase-1/2 signaling and is involved in CCL21-driven B-cell chronic lymphocytic leukemia cell invasion and migration

Abstract: B-cell chronic lymphocytic leukemia (B-CLL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 20 publications
6
73
0
Order By: Relevance
“…These results suggest that the activation of ERK1/2 was involved in CCR7 mediated migration and invasion of BE1 cells. The similar report has been found in B-cell chronic lymphocytic leukemia cell, 26 in which the activation of ERK1/2 signaling pathways is involved in CCL21-driven invasion and migration. But Jun Wang et al 27 have been shown that CCR7 activate phosphoinsitide-3 kinase (PI3K)-mediated invasive pathway in head and neck cancer cells.…”
Section: Discussionsupporting
confidence: 66%
“…These results suggest that the activation of ERK1/2 was involved in CCR7 mediated migration and invasion of BE1 cells. The similar report has been found in B-cell chronic lymphocytic leukemia cell, 26 in which the activation of ERK1/2 signaling pathways is involved in CCL21-driven invasion and migration. But Jun Wang et al 27 have been shown that CCR7 activate phosphoinsitide-3 kinase (PI3K)-mediated invasive pathway in head and neck cancer cells.…”
Section: Discussionsupporting
confidence: 66%
“…However, compared with CXCR4, less is known about the role of CCR7 in regulating the secretion of MMPs. The first research on the relationship between CCR7 and MMPs was performed by Redondo and colleagues [32] . Redondo showed that MMP-9 was regulated by CCL21, the ligand of CCR7, and MMP-9 was involved in B-cell chronic lymphocytic leukemia nodal infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that ovarian CD133 þ cells and CD133 À cells have distinct patterns of chemokine and chemokine receptor expression. Several chemokines and chemokine receptors showed much stronger expression in CSLCs than in non-CSLCs; notably, many of these molecules have been reported to play important roles in tumor growth and metastasis in various cancers [42][43][44][45][46]. Previously, several groups have identified CXCR4…”
Section: Discussionmentioning
confidence: 99%